Fundamental limit of detection of photonic biosensors with coherent phase read-out - Molina-Fernández, Íñigo; Leuermann, Jonas; Ortega-Moñux, Alejandro; Wanguemert-Pérez, Juan Gonzalo; Halir, Robert (Optica Publishing Group, 2019)
Photonic biosensors oﬀer label-free detection of biomolecules for applications rangingfromclinicaldiagnosistofoodqualitymonitoring. BothsensorsbasedonMach-Zehnder interferometers and ring resonators are widely used, but are usually read-out using diﬀerent schemes, making a direct comparison of their fundamental limit of detection challenging. A coherent detection scheme, adapted from optical communication systems, has been recently showntoachieveexcellentdetectionlimits,usingasimplefixed-wavelengthsource. Herewe present, for the first time, a theoretical model to determine the fundamental limit of detection of suchacoherentread-outsystem,forbothinterferometricandresonantsensors. Basedonthis analysis,weprovideguidelinesforsensoroptimizationinthepresenceofopticallossesandshow thatinterferometricsensorsarepreferableoverresonantstructureswhenthesensorsizeisnot limited bythe available samplevolume.
Keywords: Detectores; Coherent read-out; Sensors; Silicon photonics